2003
DOI: 10.1093/humrep/deg429
|View full text |Cite
|
Sign up to set email alerts
|

Fetal abnormalities produced after preimplantation exposure of mouse embryos to ammonium chloride

Abstract: These results support the conclusion that abnormal preimplantation culture conditions can cause fetal abnormalities in mice, but the risks may be lower than previously suggested. Further work is needed to evaluate the risk more fully but this risk should be considered when designing new strategies for human assisted conception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…Since the report of ammonium build-up in a culture medium due to L-glutamine [7], several reports have shown that the presence of ammonium ion in a culture medium decreases the cell numbers of the blastocyst and inner cell mass, increases apoptosis, perturbs development after implantation of murine embryos [11,12] and causes fetal abnormalities [10]. These data suggest that EA and BA, in which ammonium build-up has not been detected, do not impair the developmental competence of human embryos compared with BASI and II, in which ammonium build-up has been detected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the report of ammonium build-up in a culture medium due to L-glutamine [7], several reports have shown that the presence of ammonium ion in a culture medium decreases the cell numbers of the blastocyst and inner cell mass, increases apoptosis, perturbs development after implantation of murine embryos [11,12] and causes fetal abnormalities [10]. These data suggest that EA and BA, in which ammonium build-up has not been detected, do not impair the developmental competence of human embryos compared with BASI and II, in which ammonium build-up has been detected.…”
Section: Discussionmentioning
confidence: 99%
“…The build-up of ammonium is principally derived from the spontaneous breakdown of glutamine under conditions used for the culture of preimplantation embryos [9]. Several groups of researchers have also suggested that ammonium in media has a deleterious effect on the mouse fetus after embryo transfer [10][11][12].…”
mentioning
confidence: 99%
“…The supply of high levels of protein or urea periconception increases reproductive tract ammonium levels [17,18], allowing inferences to be drawn from studies investigating ammonium exposure during embryo development that show reduced blastocyst cell numbers and increased apoptosis [19]. The developing fetus and placenta also are influenced by periconception dietary protein supply, including a reduction in pregnancy rates [15], altered fetal development and abnormalities [15,20,21], reduced placental weight and size [7,22], and altered imprinted gene expression in fetal tissue [15,23]. Although evidence to date implicates a lowprotein diet (LPD) in rodents with perturbed embryo, fetal, and offspring development, comparatively less work has focused on the consequences of a high-protein diet (HPD) similar to that consumed in popular weight-loss programs [24].…”
Section: Introductionmentioning
confidence: 99%
“…USP14 deficiency in mice has been linked to neuronal dysfunction, and a reduction in levels of the protein following gene knockout in transgenic mice subsequently leads to male sterility (Crimmins et al 2009). Given that one of the gross manifestations of ammonium toxicity after transfer in the mouse is the development of exencephaly (Lane & Gardner 1994, Sinawat et al 2003, the altered gene expression profile reported herein may indicate a possible aetiology of this neural tube defect. In the human blastocyst, increased expression of nicotinamide N-methyltransferase (NNMT), which catalyses the N-methylation of nicotinamide and structurally related pyridines, was also observed.…”
Section: Discussionmentioning
confidence: 88%
“…The activity of this shuttle is essential for the regulation of metabolism during the preimplantation period (Lane & Gardner 2005a), and if its activity is compromised in the blastocyst, then subsequent implantation and fetal development are significantly reduced (Mitchell et al 2009). The alterations in the gene expression of Got1 observed in the presence of ammonium could, therefore, be associated with compromised metabolic activity and regulation and may well be a causative factor for the reduced viability of mouse embryos exposed to ammonium (Lane & Gardner 1994, Sinawat et al 2003. Across the two species studied, both revealed a decrease in the expression of ubiquitin-specific proteases (USPs).…”
Section: Discussionmentioning
confidence: 99%